Movimenti di protesta agraria e populismo nel Sud degli Stati Uniti, 1877-1896 - Lerda Gennaro, Valeria (Studi americani, 2016)
Movimenti di protesta agraria e populismo nel Sud degli Stati Uniti, 1877-1896